EFFECT OF ATTENDANCE LEVEL AND WORK MOTIVATION ON EMPLOYEE WORK PRODUCTIVITY AT PT. ADI ACTIVE MAP MIGHTY FIELD - Andri Ekawati, Yuni; Suryana, Suryana (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to determine whether there is an effect of attendance and work motivation on employee productivity at PT. Adi Perkasa Medan's Active MAP and how much influence it has. The method used in this study is a quantitative method with several tests, namely reliability analysis , classical assumption deviation test and linear regression . Based on the results of the primary data regression which was processed using SPSS 18, the following multiple linear regression equation was obtained: Y = 13.937 + 0.584 X 1 +0.722 X 2. Partially, the attendance level variable (X 1 ) has a positive and significant effect on the work productivity of PT. MAP Active Adi Perkasa Medan . This means that the hypothesis in this study is accepted, as evidenced by the value of t count < t table (4.682 > 1.691). While the work motivation variable (X 2 ) has a positive and significant influence on the work productivity of PT. MAP Active Adi Perkasa Medan . This means that the hypothesis in this study is accepted, as evidenced by the value of t count > t table (4.017 > 1.691). Simultaneously, the variables of attendance (X1 ) and work motivation (X2 ) have a positive and significant influence on the work productivity of PT. MAP Active Adi Perkasa Medan . This means that the hypothesis in this study is accepted, as evidenced by the calculated F value > F table (17,392 > 3,26 ) . Variables of attendance level (X1 ) and work motivation (X2 ) were able to contribute to the influence of the employee productivity variable by 50.6% while the remaining 49.4% was influenced by other variables not examined in this study. From the conclusions above, the authors suggest that in terms of attendance levels, employees are no longer lazy to come to work and do absenteeism without explanation so that employee productivity does not decrease. The work motivation given by the leadership is very necessary so that employees can work with enthusiasm. Employees should work well according to procedures and regulations so that company leaders are satisfied.